Indução da embriogênese somática de Jenipapeiro - Nascimento, Larissa Luzia Peixoto (2022)
Somatic embryogenesis is a tissue culture technique that makes genetic resources conservation and the propagation of plant species on a large scale possible. For Genipa americana L., this technique can make commercial propagation and production feasible, minimize the genetic drift caused by extractivism, currently the only form of exploitation, and promote the use of this crop in large industrial sectors. Given the above, this study tested somatic embryogenesis in genipap. The experiment was divided into two stages: the first analyzed leaf and nodal explants of the accession UMB, cultivated in a primary medium of half strength Murashige and Skoog salts (½ MS) with 30 g/L sucrose, 400 mg/L malt extract and 3 g/L gelling agent Phytagel®, plus all 16 possible combinations between the growth regulators naphthaleneacetic acid (NAA) and benzylaminopurine (BAP) and concentrations of 0.0; 4.0; 6.0 and 8.0 mg/L. After 40 days, the percentage of callus coverage and callus types were evaluated on a 0 - 3 score scale. After 90 days in the dark, the culture was transferred to the secondary medium (primary medium + 10 µM 2,4-D) with a 12-h photoperiod. After 50 days in the secondary medium, the presence of embryogenic calli was evaluated and osmotic stress maturation induced with different Phytagel® concentrations (3, 5, 7 and 9%). The second step consisted of the cultivation of leaf explants from five genipap populations (UMB, JSA, SC, CER and SAL) in primary medium plus three combinations of NNA and BAP regulators (4.0/4.0; 4.0/6.0 and 6.0/4.0 mg/L NNA and BAP, respectively). For 60 days, every 10 days, the fresh weight increase of the calli was evaluated to establish the growth curve and assess embryogenic callus development. Callus induction at scores above 2.5 was considered promising. Characteristics of type 1 calli were observed, which could possibly generate embryogenic and type 2 calli. Type 1 calli developed better in the presence of growth regulators, i.e., from the nodal segments, at concentrations of 8.0 mg/L BAP and 6.0 mg/L NNA, and from the leaf explants at 8.0 mg/L NNA. Induction of type 2 calli at 100% occurred only in nodal segments in the absence of NNA and BAP and in the presence of 4.0 and 6.0 mg/L NNA. The concentration of 6.0 mg/L BAP promoted induction of embryogenic calli in the preliminary assay with accession UMB. Accession SAL developed more (100%) embryogenic calli than the others in response to the three above regulator combinations, confirmed by cytochemical analyses with acetic carmine and Evans blue. The growth curve reached the lag, exponential and stationary phases after 60 days of in vitro culture. No significant effects of the tested Phytagel® concentrations on embryo maturation were observed.